On solvability of the BVPS for the fourth‐order Emden‐Fowler type equations - Yermachenko, Inara (Mathematical Modelling and Analysis, 2007)
Solvability of the boundary value problems (BVPs) for the fourth‐order Emden‐Fowler type equations x (4) = q(t)|x| p sgn x is investigated by using the quasilinearization process. We modify the equation to a quasi‐linear form x( 4) – k 4 x = Fk (t,x) for various values of k. Our considerations are based on a fact that the modified quasi‐linear problem has a solution of the same oscillatory type as the linear part x (4) – k 4 x has. We show that original problem in some cases also has a solution of definite type and establish sufficient conditions for multiple solutions of the given BVP.First Published Online: 14 Oct 2010